Human Factors in medicine : Leadership, cooperation behavior and team performance - (:unkn) unknown (My University, 2025)
Human Factors in medicine : Leadership, cooperation behavior and team performance
Keywords: Human factors; Resuscitation; Teamwork; Leadership